Performance in enhancement of microfluidic-based capacitive pressure sensor - Muhammad Rashidi Ab Razak (Tanjong Malim, 2020)
Performance in enhancement of microfluidic-based capacitive pressure sensor by Muhammad Rashidi Ab Razak